Integration of Logistics 4.0 And Industry 4.0 Into Logistics Management: Challenges and Opportunities - Bayar, Munevver (Journal of Ecohumanism, 2023)
The term Industry 4.0 generally refers to intelligent digitalization, the automation of products and value chain processes, and the integration of real and virtual production worlds where products, factories, people, and objects are integrated with embedded software in smart, distributed systems. The fourth industrial revolution encompasses numerous application examples in diverse fields, from healthcare to industry. However, unlike other sectors, despite the increasing strategic importance of digitalization for businesses in a changing and competitive environment, impacting established processes, business models, and industry boundaries, as well as having an ecological impact, it has been observed that logistics businesses are not sufficiently interested in this topic.The new trade strategies outlined in the United Nations' development plan focus particularly on sustainability in the industrial sector. The most effective way to keep up with the rapidly evolving technology driven by the fourth industrial revolution, and particularly to ensure sustainability in manufacturing businesses, is to integrate Logistics 4.0 into the business. Looking at today's business world, it's clear that the continuous advancement of technology has led to significant development and change in the logistics sector.In this context, the research aims to thoroughly examine the contributions of Industry 4.0 implementation to operational efficiency in the logistics sector. The theoretical part was conducted through a literature review, providing information without going into detail, while the practical part was developed through a survey and data analysis using SPSS.